Photoelectrochemical Solar Fuel Production From Basic Principles to Advanced Devices - Giménez, Sixto; Bisquert, Juan (Springer International Publishing : Imprint: Springer, 2016)
This book explores the conversion for solar energy into renewable liquid fuels through electrochemical reactions. The first section of the book is devoted to the theoretical fundamentals of solar fuels production, focusing on the surface properties of semiconductor materials in contact with aqueous solutions and the reaction mechanisms. The second section describes a collection of current, relevant characterization techniques, which provide essential information of the band structure of the semiconductors and carrier dynamics at the interface semiconductor.  The third, and last section comprises the most recent developments in materials and engineered structures to optimize the performance of solar-to-fuel conversion devices.